The Rural Woman Speaks in 1970s Argentina - Julia Sarreal (Latin American Research Review, 2024)
Studies of the “people’s spring,” the period of unprecedented social mobilization in Argentina in the early 1970s, frequently omit rural women even though they were among the sectors that rallied for social justice. In most of Latin America at the time, rural women were prevented from equal participation in social movements; in contrast, rural women in northeastern Argentina actively participated in the Movimiento Agrario Misionero (MAM). This article uses letters and newspaper articles in Amanecer agrario to answer two questions: First, what did womanhood mean for rural women in northeastern Argentina during the early 1970s? Second, what did the “people’s spring” mean for these same women? Although the movement split, with women from small farms generally wanting MAM to expand its efforts to broader societal problems and women from medium farms generally wanting MAM to stay focused on the concerns of Misiones farmers, throughout it all, rural women communicated their hopes, desires, and concerns for themselves, their families, and their communities.